On the consistency conditions to braneworlds in scalar-tensor gravity for arbitrary dimensions - Abdalla, M. C B [UNESP]; Guimarães, M. E X; Hoff Da Silva, J. M. [UNESP] (My University, 2009)
We derive an one-parameter family of consistency conditions to braneworlds in the Brans-Dicke gravity. The General Relativity case is recovered by taking a correct limit of the Brans-Dicke parameter. We show that it is possible to build a multiple AdS brane scenario in a six-dimensional bulk only if the brane tensions are negative. Besides, in the five-dimensional case, it is showed that no fine tuning is necessary between the bulk cosmological constant and the brane tensions, in contrast to the Randall-Sundrum model. Copyright © owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial- ShareAlike Licence.
Keywords: Arbitrary dimension; Brans-Dicke gravities; Consistency conditions; Cosmological constants; Fine tuning; General Relativity; One parameter family; Randall-Sundrum; Relativity; Gravitation